2002
DOI: 10.1074/jbc.m107027200
|View full text |Cite
|
Sign up to set email alerts
|

Residues 88–109 of Factor IXa Are Important for Assembly of the Factor X Activating Complex

Abstract: Activated platelets and phospholipid vesicles promote assembly of the intrinsic factor X (FX) activating complex by presenting high-affinity binding sites for blood coagulation FIXa, FVIIIa, and FX. Previous reports suggest that the second epidermal growth factor (EGF) FIXa is a serine protease that participates in the intrinsic pathway of blood coagulation. FIXa activates FX as part of the intrinsic FX activating complex. The FX activating complex consists of FIXa, FVIIIa (a nonenzymatic cofactor), and FX (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…We also noted that clotting was not affected by insertion of the R94D mutation. Our results are in line with those demonstrating that R94D is not important for assembly of the Xase complex on phospholipid vesicles (41). We believe that the results from our experiments show that the Glu 78 -Arg 94 salt bridge is not essential for maintenance of the FIX structure but that other interactions in this area are sufficient to maintain proper alignment of the light chain domains.…”
Section: ϫ9supporting
confidence: 82%
“…We also noted that clotting was not affected by insertion of the R94D mutation. Our results are in line with those demonstrating that R94D is not important for assembly of the Xase complex on phospholipid vesicles (41). We believe that the results from our experiments show that the Glu 78 -Arg 94 salt bridge is not essential for maintenance of the FIX structure but that other interactions in this area are sufficient to maintain proper alignment of the light chain domains.…”
Section: ϫ9supporting
confidence: 82%
“…1) to identify "candidate" residues that are highly conserved among species and different from those in FVII, because residues in FVII molecules have been shown to be ineffective in mediating platelet surface-mediated FX activation complex assembly (2,6). Recombinant FIXa point mutants in loop 1 (N89A, I90A, K91A, and R94A) and loop 2 (D104A, N105A, and V107A) were prepared to study the contributions of these residues to FX activation complex assembly on activated platelets.…”
Section: Discussionmentioning
confidence: 99%
“…However, this contribution is considered to be structural rather than direct, because the segment FIXa variants showed normal FVIIIa binding in surface plasmon resonance experiments (36). Kinetic studies using recombinant FIXa chimeras have consistently shown that residues in the EGF2 domain do not mediate FVIIIa association suggested by both normal kinetic stimulation by FVIIIa and normal K d(app)FVIIIa values (2)(3)(4)6). Thus, the contribution of the non-catalytic domain of FIXa to its interaction with FVIIIa appears to be mainly structural, i.e.…”
Section: Egf2 Domain Of Fixa In Fx Activation On Plateletsmentioning
confidence: 99%
See 2 more Smart Citations